(untitled) (المجلة الدولية للبحوث العلمية, 2023)
Introduction: The rapid advancement of medical devices has significantly influenced healthcare delivery, necessitating an understanding of healthcare workers’ attitudes towards these technologies. This systematic review aimed to explore healthcare workers’ attitudes toward medical devices, focusing on the factors influencing these attitudes and the impact on technology adoption and utilization in clinical settings. Methods: A comprehensive search of electronic databases including PubMed, Scopus, Web of Science, and the Cochrane Library was conducted, focusing on observational studies published in the last five years up to 2022. The review included studies that assessed healthcare workers’ attitudes towards medical devices, with a particular focus on cross-sectional studies. Inclusion and exclusion criteria were applied to select relevant studies, and data extraction focused on key outcomes such as positivity rates towards medical devices, concerns about data security, and the perceived need for training and support. Results: The systematic review, encompassing seven clinical trials, elucidates the effectiveness of physiotherapy interventions for individuals recovering from head and neck trauma, with sample sizes ranging from 52 to 764 participants. The diverse demographic characteristics and trauma types, including fractures and sports-related incidents, highlight the broad applicability of the findings. The interventions, spanning exercises to therapeutic modalities, yielded favorable outcomes, evidenced by risk ratios indicating a 24% reduction in pain scores, a 34% improvement in range of motion, and a 21% increase in functional outcomes, supported by robust confidence intervals [6, 10-14]. These results collectively emphasize the positive impact of physiotherapy interventions on head and neck trauma recovery. Conclusions: Healthcare workers generally demonstrate a positive outlook towards medical devices, acknowledging their potential to improve patient care. Nonetheless, addressing concerns related to data security and the need for comprehensive training and support is essential for fostering broader acceptance and effective utilization of these technologies in clinical practice. Efforts to enhance healthcare workers’ confidence in using medical devices could lead to improved patient outcomes and more efficient healthcare delivery.